Determination of Se(IV) in Pharmaceuticals by Using Different Operating Modes of Pulse Anodic Stripping Voltammetric Analysis with Methylene Blue-Nafion Modified Gold Electrode - Aziz Ramadan, Abdul; Mandil, Hasna; Ozoun, Amer (Asian Journal of Chemistry, 2013)
Determination of selenium(IV) in Syrian pharmaceuticals with a methylene blue-nafion modified gold electrode by using different operating modes of pulse anodic stripping voltammetry : with constant amplitude of negative (PASVNP) or positive (PASVPP) polarity, imposed pulses of linearly increasing amplitude (PASVLIA) and differential sampling on successive pulses (DI/Dt) was applied. Selenium(IV) was determined in an aqueous HClO4 medium (1 M) at an accumulation potential of -240 mV and an accumulation time of 300s. The potential was scanned from 0.0 to 1250 mV using auto-scan facility. The peak potential was measured at 1000-1010, 1030-1040, 1130-1140 and 1030-1060 mV and the calibration curve for Se(IV) under optimized conditions was linear in the ranges 7.896-78.96, 23.688-118.44, 23.688-118.44 and 0.7896-78.96 ng mL-1 for operating modes PASVNP, PASVPP, PASVLIA and DI/Dt, respectively. RSD was less than 5 %. The methods were applied to the determination of Se(IV) in Syrian pharmaceuticals with high sensitivity and accuracy. The results obtained by pulse anodic stripping voltammetry methods were validated by atomic absorption spectroscopy with hydride generation.